Outsourcing, labor regulations and profit-sharing: Evidence from Mexico - Agustina Colonna; Lorenzo Aldeco Leo (Banco de México, 2025)
This paper studies the use of domestic outsourcing to circumvent labor benefits and its consequences for firms and workers. Drawing on longitudinal establishment data and employer-employee data from Mexico, we provide evidence that many firms were outsourcing their entire workforce to avoid mandatory profit-sharing. A model shows that the incentive for this practice arises when firms face a labor supply curve that is less elastic to profit-sharing than to wages. We then leverage a reform that restricted outsourcing to assess the model predictions. The reform caused previously-outsourcing establishments to insource their workers and comply with profit-sharing, with no evidence of an effect on total employment. Treated plants partially offset the profit-sharing increase through lower wage growth, yet total worker compensation increased, consistent with our model. Self-collected survey evidence suggests that inelasticity to profit-sharing is partly explained by information frictions among workers, implying that they benefited from the reform.
Keywords: J08; J41; O12; O14; 330; Outsourcing; Profit-sharing; Labor Market; Market Power